A-19 Distress Predicts Poorer Cognitive Performance At Post-Injury In Concussed Athletes. (13th July 2022) - Hansen, J; Mrazik, M; Wagner, R; Ree-Fedun, Q; David, C; Arends, P; Varkovestski, M; Naidu, D
Abstract: Purpose: This study evaluated the consistency between athletes' self-reported cognitive symptoms and cognitive test performance. Methods: The sample included 784 Canadian Football League athletes who underwent standardized cognitive testing with cognitive testing (ImPACT) and the Brief Symptom Inventory (BSI-18) at baseline. Over 2 consecutive seasons, 46 players were diagnosed with concussions following assessment with team physicians within 48 hours; 10 were eliminated due to missing data. Five cognitive symptoms (feeling slowed down, feeling in a fog, not feeling right, difficulties concentration, difficulties with memory) were used to create a composite score (Cog). The Cog index, the depression, anxiety, total index scores from the BSI, and the 5 ImPACT cognitive domains were correlated at baseline and post-injury. History of learning disabilities, ADHD, psychiatric diagnosis, and history of concussion were co-variates. Results: There were no significant correlations between Cog, depression, anxiety or total BSI scores and the ImPACT cognitive domains at baseline. At post injury there were no significant correlations between Cog or ImPACT index scores. In contrast, significant negative correlations were found between BSI Anxiety and verbal memory (r = 0.67, p < 0.01), visual memory (r = 0.68, p < 0.01), and visual-motor processing speed (r = 0.48, p < 0.05). In addition, there were significant negative correlations between the BSI total score and visual memory (r = 0.51, p < 0.05) and reaction time (r = 0.55, p < 0.05). Conclusions: Self-reported cognitive difficulties do not correlate with poorer cognitive outcomes in our sample of professional football players. However, distress at post-injury was significantly correlated to performance, suggesting psychological variables may play a role in cognitive functioning.